Lichenoid infiltrate in oral submucous fibrosis: A new marker of malignant transformation. (January 2022) - Sarode, Gargi S.; Sarode, Sachin C.; Yuwanati, Monal; Gadbail, Amol; Gondivkar, Shailesh
Highlights: Prediction of MT in OPMDs is a greatest challenge for the investigators. Any consistent feature at surgical margins can be a vital prognostic marker for MT. Inflammation similar to lichenoid infiltrates is linked to a poor prognosis in OSCC. Lichenoid infiltrate OSF could be an indictor for initiation of MT in OSF.